Galactic explorer for learning education: galexio space game / Ahmad Haziq Ros Hamdan ... [et al.] - Ros Hamdan, Ahmad Haziq; Ahmad Nazori, Muhammad Wa'ie; Mohammed, Mohammad Shahniezam; Adnan, Muhammad Amirul Hakim; Aziz, Siti Maisarah (2020)
Educational games for children have been widely used in supporting learning in-side and out of school and a growing interest have appeared for the potential to deliver effective and engaging learning experiences. Educational games are important elements to maintain children interest motivation and immersion. There is variety of educational board games and that intend to assist users to achieve various educational goals. However, the present popular board games such as Monopoly, Uno and Sahiba are fun rather than learning centered. In order to overcome this problem, an innovative board game namely Galexio Space Game is designed to cater both fun and learning. The game set consists of dice, nine planets, solar systems set of questions, buying-trading stars and it needs at least two players.This educative game would inculcate interest in astronomy among children and has a potential to be patented and commercialized.